2018
DOI: 10.1002/pbc.27384
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Interdisciplinary Tumor Board of the Cooperative Ewing Sarcoma Study Group on local therapy and overall survival of Ewing sarcoma patients after induction therapy

Abstract: As a reference center for a rare disease, recommendations from our ITB impacted local therapy and led to higher OAS in patients with metastatic disease. To our knowledge, this is the first analysis that examines the value of a reference tumor board on a rare disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 38 publications
0
37
0
3
Order By: Relevance
“…In the present study, there was a high incidence of metastatic disease at presentation (50.70%). Pakos et al 30 , in an international OS compilation, where OS Brazilian Group was included, showed 13% of the patients with metastatic disease, the same could be seen in the OS Children Oncology Group (COG) (27%) and Cooperative Ewing Sarcoma Study (CESS) group (30%) [30][31][32][33][34] . Patients arrived at INCA with advanced disease and this characteristic probably influenced in their pain status in all follow-up moments.…”
Section: Discussionmentioning
confidence: 73%
“…In the present study, there was a high incidence of metastatic disease at presentation (50.70%). Pakos et al 30 , in an international OS compilation, where OS Brazilian Group was included, showed 13% of the patients with metastatic disease, the same could be seen in the OS Children Oncology Group (COG) (27%) and Cooperative Ewing Sarcoma Study (CESS) group (30%) [30][31][32][33][34] . Patients arrived at INCA with advanced disease and this characteristic probably influenced in their pain status in all follow-up moments.…”
Section: Discussionmentioning
confidence: 73%
“…We have shown there is almost universal use of MDT discussion, and adoption of a wide range of existing treatment protocols. Wide discussion outside the treating MDT, for example in a national forum or with another centre is not usual in the majority of countries, although the EICESS 92 experience indicates that a more unified approach could be explored to determine if it will improve outcomes for patients and has been adopted by the CESS group in Germany [ 4 , 10 ]. The wider adoption of national or international MDT discussions has some intuitive appeal but demands further evidence.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that utilization of a specialized IDTB improves relapse-free survival in sarcoma patients [14]. A study in patients with Ewing sarcoma showed increased overall survival when using a specialized reference board [19]. We were not able to measure the use of specialized sarcoma boards in German sarcoma patients directly and only measured that of IDTB in general.…”
Section: Tumor Board Utilizationmentioning
confidence: 96%